Bio-Inspired Functional Surfaces Based on Laser-Induced Periodic Surface Structures - Müller, Frank A. (Materials (Basel), 2016)
Nature developed numerous solutions to solve various technical problems related to material surfaces by combining the physico-chemical properties of a material with periodically aligned micro/nanostructures in a sophisticated manner. The utilization of ultra-short pulsed lasers allows mimicking numerous of these features by generating laser-induced periodic surface structures (LIPSS). In this review paper, we describe the physical background of LIPSS generation as well as the physical principles of surface related phenomena like wettability, reflectivity, and friction. Then we introduce several biological examples including e.g., lotus leafs, springtails, dessert beetles, moth eyes, butterfly wings, weevils, sharks, pangolins, and snakes to illustrate how nature solves technical problems, and we give a comprehensive overview of recent achievements related to the utilization of LIPSS to generate superhydrophobic, anti-reflective, colored, and drag resistant surfaces. Finally, we conclude with some future developments and perspectives related to forthcoming applications of LIPSS-based surfaces.